Some Human Factors Problems and Possibilities in Developing Ethiopia - Messing, S.D. (Human Factors: The Journal of Human Factors and Ergonomics Society, 1968)
Both negative and positive cultural factors affect innovative efforts in developing countries. In the case of Ethiopia, negative factors include a low esteem for craftsmanship. Even where modern education is making inroads on some negative factors, as in the towns, feudalistic attitudes toward labor and the preference for unskilled labor on the assumption that it is more economical, act to continue functionally inefficient attitudes. In contrast, positive factors exist in traditions of mutual aid, now spreading from South Ethiopian cultures northward. An excellent model for mutual aid may be found in the practices of the migrant weavers' association of the Gurage and some neighboring tribes. Ethiopia provides an interesting area for the study of human factors in developing countries since it has not passed through a colonial period. Various stages of development can be traced comparatively free of outside influences. © 1968, Human Factors and Ergonomics Society. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.ant